Dual Burden of Weight among College Entrants at Kancheepuram, Tamil Nadu - S Keerthana; Somnath Verma; Bhavishya Sundar; P Padmanabhan; N Dinakaran (Journal of Epidemiology and Public Health, 2024)
Background: Body Mass Index (BMI) is a good indicator of health and well-being. Even though it does not accurately measure body fat, BMI is advocated as a simple instrument for identifying obesity. Obesity is a global public health problem with ever-increasing incidence. The data on the regional distribution of BMI, an index of health will be useful in the case of healthcare policy formulation. This study aimed to provide data about the frequency distribution of BMI among adolescents and young adults in Kancheepuram, Tamil Nadu, India.Subjects and Method: This was a cross-sectional study conducted at Kancheepuram, Tamil Nadu, in September 2023. A total of 1,050 college students was selected using convenience sampling. The dependent variable was BMI. The independent variables were age and sex. The classification of BMI was based on Asian Indian criteria, supplemented by WHO guidelines.Results: Obesity among males was 2.93% according to WHO criteria and 9.56% according to the Asian Indian modification, while for females, obesity was 3.03% by WHO criteria and 10.98% by the Asian Indian modification. Based on Asian Indian criteria, 27.90% of the sample was classified as underweight, 8.85% as overweight, and 20.66% as obese.Conclusion: The problem of overweight and obesity needs public health attention since this is preventable